2021
DOI: 10.1155/2021/9646932
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical, Endoscopic, and Pathological Findings among Suspected Peptic Ulcer Disease Patients in Abuja, Nigeria

Abstract: Background. Peptic ulcer disease (PUD) remains one of the most prevalent gastrointestinal diseases and has been linked to Helicobacter pylori (H. pylori) infection. This condition may be suspected on clinical grounds, but diagnosis is established using upper gastrointestinal endoscopy. Aims. To determine the correlation between the endoscopic and pathological findings among suspected PUD patients who have been referred for diagnostic upper gastrointestinal endoscopy in National Hospital Abuja. Methods. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These findings were congruent with hospital-based sub-Saharan African (SSA) reports. The African reports verified that 40–65% of dyspeptic and 65–90% PUD patients were positive for H. pylori infection [ 7 , 8 , 19 , 20 , 23 , 24 ]. The Ethiopian pooled prevalence of H. pylori infection was 52.2% (95% CI 45.8–58.6) in a recent hospital-based meta-analysis [ 30 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These findings were congruent with hospital-based sub-Saharan African (SSA) reports. The African reports verified that 40–65% of dyspeptic and 65–90% PUD patients were positive for H. pylori infection [ 7 , 8 , 19 , 20 , 23 , 24 ]. The Ethiopian pooled prevalence of H. pylori infection was 52.2% (95% CI 45.8–58.6) in a recent hospital-based meta-analysis [ 30 ].…”
Section: Discussionmentioning
confidence: 96%
“…Recent Nigerian study reported that gastritis/duodenitis (27%) and PUD (28%) were the frequently documented abnormal endoscopic findings. Gastric cancer (2.3%) was less frequently reported [ 7 ]. Studies in Tanzania and Ethiopia reported that gastritis/duodenitis (80–98%) followed by PUD (25–32%) were the commonly observed endoscopic pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study's finding of UGIB being more common in males is consistent with that from several authors (2, 5-7). The male preponderance may be explained by the higher prevalence of the underlying diseases and risk factors in Nigerian males, namely alcohol, smoking, peptic ulcers, and chronic liver disease (12)(13)(14)(15). Thirty-three percent of the patients with UGIB in our study were at least 60 years.…”
Section: Discussionmentioning
confidence: 66%